A comparison of interannual hydrological polar motion excitation from GRACE and geodetic observations. (September 2016) - Meyrath, T.; van Dam, T.
Abstract: Continental hydrology has a large influence on the excitation of polar motion (PM). However, these effects are far from being completely understood. Current global water storage models differ significantly from one another and are unable to completely represent the complex hydrological cycle, particularly at interannual scales. A promising alternative to study hydrological effects on PM is given by the GRACE satellite mission. In this study, we assess the ability of GRACE to investigate interannual hydrological PM excitations. For this purpose, we use the latest GRACE Release-05 data from three different processing centers (CSR, GFZ, JPL) that we convert into estimates of hydrological PM excitation, χ 1 H and χ 2 H . In addition to these gravimetric excitations, we also consider geodetic hydrological excitations, which we calculate by removing modelled atmospheric and oceanic effects from precise observations of full PM excitations. We remove signals with frequencies ≥1 cpy from the series and compare the resulting estimates of interannual hydrological excitations for the period 2004.5–2014.5. The comparison between geodetic and gravimetric excitations reveals some discrepancies for χ 1 H, likely to be related to inadequately modelled atmospheric and oceanic effects. On the other hand, good agreement is observed for χ 2 H . For both components, the best agreement between geodetic and gravimetric excitations is obtained for the estimate from CSR. Very good agreement is obtained between GRACE-derived excitations from different processing centers, in particular for CSR and JPL. Both the comparisons between geodetic and gravimetric, and the comparisons between the different gravimetric excitations give substantially better results for χ 2 H than for χ 1 H, leading to the conclusion that geodetic and gravimetric χ 2 H can be more reliably determined than χ 1 H . Although there are still some discrepancies between geodetic and gravimetric interannual hydrological excitations, we conclude that GRACE and potential follow-on missions are valuable tools to study the interannual effects of continental hydrology on the excitation of PM.